2015
DOI: 10.1615/critrevtherdrugcarriersyst.2015012360
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dots and their Potential Role in Cancer Theranostics

Abstract: The emergence of cancer nanomedicine is the result of fruitful advances in the fields of nanotechnology, bioimaging, formulation development, and molecular biology. Quantum dots (QDs) are the luminescent nanocrystals (NCs) that provide a multifunctional platform for imaging the biosystems following controlled delivery of therapeutic drugs, proteins, peptides, oligonucleotides, and genes. These engineered fluorescent probes with integrated imaging and carrier functionalities have become excellent tools for mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Diagnostic and targeted affinity molecular imaging can be obtained by nanoscaled advanced materials, including: quantum dots (QDs), 24,51 solid lipid nanoparticles (SLNs), 5,52 liposomes, 33,53 metallic NPs, dendrimeric and polymeric NPs, 54 carbon nanotubes, 55 micelles, 56,57 and iodinated NPs. 58,59 Biologically, appropriate synchronic molecular reactions, such as sufficient adhesion strength with cell, are essential for NPs/NSs intended for overcoming hydrodynamic forces persuaded via blood circulation and remaining on cell surface in the living organisms.…”
Section: Imaging Techniques Used For Diagnosismentioning
confidence: 99%
“…Diagnostic and targeted affinity molecular imaging can be obtained by nanoscaled advanced materials, including: quantum dots (QDs), 24,51 solid lipid nanoparticles (SLNs), 5,52 liposomes, 33,53 metallic NPs, dendrimeric and polymeric NPs, 54 carbon nanotubes, 55 micelles, 56,57 and iodinated NPs. 58,59 Biologically, appropriate synchronic molecular reactions, such as sufficient adhesion strength with cell, are essential for NPs/NSs intended for overcoming hydrodynamic forces persuaded via blood circulation and remaining on cell surface in the living organisms.…”
Section: Imaging Techniques Used For Diagnosismentioning
confidence: 99%
“…Quantum dots are a subclass of fluorescent nanomaterials, which have unique chemical and physical properties compared to organic dyes [89]. They have been utilized as multifunctional nanocarriers for PDT thanks to their high quantum yields, simple surface modification, and tunable optical properties [90]. They are also excellent donors in fluorescence resonance energy transfer (FRET) applications [91].…”
Section: Semiconductor Quantum Dots (Qds)mentioning
confidence: 99%
“…The above QD-based BC PDT studies have paved a new avenue for researchers to synthesize various targeted-QDs against breast cancer. It has been reported that QDs have potential cytotoxicity under UV irradiation to act as efficient PSs [90]. Furthermore, NIR fluorescent QDs provide improved PS water solubility, chemical stability, and low optical interference with biological tissues in PDT cancer treatments, when compared to small molecule-based PSs administered alone [94].…”
Section: Semiconductor Quantum Dots (Qds)mentioning
confidence: 99%
See 2 more Smart Citations